A theoretical study of the A2 ∑+-X2∏ system of the SiP molecule - Ornellas, F. R.; Andreazza, C. M. [UNESP]; De Almeida, A. A. (My University, 2000)
The A2∑+ and Z2∏ electronic states of the SiP species have been investigated theoretically at a very high level of correlation treatment (CASSCF/MRSDCI). Very accurate potential energy curves are presented for both states, as well as the associated spectroscopic constants as derived from the vib-rotational energy levels determined by means of the numerical solution of the radial Schrödinger equation. Electronic transition moment function, oscillator strengths, Einstein coefficients for spontaneous emission, and Franck-Condon factors for the A2∑+-X2∏ system have been calculated. Dipole moment functions and radiative lifetimes for both states have also been determined. Spin-orbit coupling constants are also reported. The radiative lifetimes for the A2∑+ state, taking into account the spin-orbit diagonal correction to the X2∏ state, decrease from a value of 138 ms at v′ = 0 to 0.48 ms at v′ = 8, and, for the X2∏ state, from 2.32 s at v″ = 1 to 0.59 s at v″ = 5. Vibrational and rotational transitions are expected to be relatively strong.
Keywords: ISM: molecules; Molecular data; Molecular processes